2021
DOI: 10.1097/corr.0000000000001724
|View full text |Cite
|
Sign up to set email alerts
|

How Long Will It Take to Reach Gender Parity in Orthopaedic Surgery in the United States? An Analysis of the National Provider Identifier Registry

Abstract: Background Although previous studies have evaluated how the proportion of women in orthopaedic surgery has changed over time, these analyses have been limited by small sample sizes, have primarily used data on residents, and have not included information on growth across subspecialties and geographic regions. Question/purpose We used the National Provider Identifier registry to ask: How have the (1) overall, (2) regional, and (3) subspecialty percentage… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
82
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 81 publications
(86 citation statements)
references
References 38 publications
4
82
0
Order By: Relevance
“…In other words, even in high gender diversity areas, there are 4.7 male orthopaedic surgeons joining practices for every one female. Our results are consistent with those found in a recent study by Acuña et al, which found that at current growth rates, it will take over 200 years to achieve gender parity (defined as at least 36.3% female) in orthopaedic surgery [ 20 ].…”
Section: Discussionsupporting
confidence: 93%
“…In other words, even in high gender diversity areas, there are 4.7 male orthopaedic surgeons joining practices for every one female. Our results are consistent with those found in a recent study by Acuña et al, which found that at current growth rates, it will take over 200 years to achieve gender parity (defined as at least 36.3% female) in orthopaedic surgery [ 20 ].…”
Section: Discussionsupporting
confidence: 93%
“…Although Title IX and the second wave of feminism led to an increase of women in medicine, orthopaedic surgery lags behind, with the lowest percentage of women among all specialties. On the basis of the current rate of women entering orthopaedic surgery, Acuña et al estimated e66 (5) it will take 326 years for the field of orthopaedic surgery to reach gender parity with the U.S. population 20 . There are orthopaedic residency programs that have yet to recruit and graduate women residents.…”
Section: Dr Claudia Thomas (1950-present)mentioning
confidence: 99%
“…1 As of April 2020, 8% of practicing orthopaedic surgeons were women and it is projected that it will take 217 years for orthopaedic surgery to achieve gender parity with the medical profession. 2 However, as a subspecialty, pediatric orthopaedics is doing relatively well. Pediatric orthopaedic fellowships enrolled a significantly greater percentage (29.52%) of female fellows than all other orthopaedic subspecialties, except oncology, from 2005-2015.…”
Section: Where Is Posna With Regard To Diversity?mentioning
confidence: 99%